Visible abdominal distension in functional gut disorders: Objective evaluation. Issue 2 (25th September 2022) - Barba, Elizabeth; Burri, Emanuel; Quiroga, Sergio; Accarino, Anna; Azpiroz, Fernando
Abstract: Background: Visible abdominal distension has been attributed to: (A) distorted perception, (B) intestinal gas accumulation, or (C) abdominophrenic dyssynergia (diaphragmatic push and anterior wall relaxation). Methods: A pool of consecutive patients with functional gut disorders and visible abdominal distension included in previous studies ( n  = 139) was analyzed. Patients (61 functional bloating, 74 constipation‐predominant irritable bowel syndrome and 4 with alternating bowel habit) were evaluated twice, under basal conditions and during a self‐reported episode of visible abdominal distension; static abdominal CT images were taken in 104 patients, and dynamic EMG recordings of the abdominal walls in 76, with diaphragmatic activity valid for analysis in 35. Key Results: (A) Objective evidence of abdominal distension was obtained by tape measure (increase in girth in 138 of 139 patients), by CT imaging (increased abdominal perimeter in 96 of 104 patients) and by abdominal EMG (reduced activity, i.e., relaxation, in 73 of 76 patients). (B) Intestinal gas volume was within ±300 ml from the basal value in 99 patients, and above in 5 patients, who nevertheless exhibited a diaphragmatic descent. (C) Diaphragmatic contraction was detected in 34 of 35 patients by EMG (increased activity) and in 82 of 103 patients by CT (diaphragmatic descent). Conclusions and Inferences: In most patients complaining of episodes of visible abdominal distention: (A) the subjective claim is substantiated by objective evidence; (B) an increase in intestinal gas does not justify visible abdominal distention; (C) abdominophrenic dyssynergia is consistently evidenced by dynamic EMG recording, but static CT imaging has less sensitivity. Abstract : In patients with functional gut disorders complaining of visible abdominal distention: distension is real, that is, patients deserve attention; excess intestinal gas, a common belief, is very unlikely; abdominophrenic dyssynergia (diaphragmatic contraction and anterior abdominal wall relaxation) is the objective cause in the majority of patients.